Age and Muscle Function Are More Closely Associated With Intracellular Magnesium, as Assessed by 31P Magnetic Resonance Spectroscopy, Than With Serum Magnesium - Cameron, Donnie; Welch, Ailsa A.; Adelnia, Fatemeh; Bergeron, Christopher M.; Reiter, David A.; Dominguez, Ligia J.; Brennan, Nicholas A.; Fishbein, Kenneth W.; Spencer, Richard G.; Ferrucci, Luigi (Frontiers in Physiology, 2019)
Total serum magnesium is a common clinical measurement for assessing magnesium status; however, magnesium in blood represents less than 1% of the body’s total magnesium content. We measured intramuscular ionized magnesium by phosphorus magnetic resonance spectroscopy (31P-MRS) and tested the hypothesis that this measure better correlates with skeletal muscle function and captures more closely the effect of aging than the traditional measure of total serum magnesium. Data were collected from 441 participants (age 24-98 years) in the Baltimore Longitudinal Study of Aging, a study of normative aging that encompasses a broad age range. Results showed that intramuscular ionized magnesium was negatively associated with age (β = −0.29, p < 0.001, R2 = 0.08) and positively associated with knee-extension strength (β = 0.31, p < 0.001, and R2 = 0.1 in women; and β = 0.2, p = 0.003, and R2 = 0.04 in men), while total serum magnesium showed no association with age or strength (p = 0.27 and 0.1, respectively). Intramuscular ionized magnesium measure was significantly lower in women that in men (p < 0.001), perhaps due to chronic latent Mg deficiency in women that is not otherwise detected by serum magnesium levels. Based on these findings, we suggest that intramuscular ionized magnesium from 31P-MRS is a better clinical measure of magnesium status than total serum magnesium, and could be measured when muscle weakness of unidentified etiology is detected. It may also be used to monitor the effectiveness of oral magnesium interventions, including supplementation.